O-glycosylation of the non-canonical T-cadherin from rabbit skeletal muscle by single mannose residues - Winterhalter, Patrick R.; Lommel, Mark; Ruppert, Thomas; Strahl, Sabine (FEBS letters, 2013)
O-mannosylation is a vital protein modification. In humans, defective O-mannosylation of α-dystroglycan results in severe congenital muscular dystrophies. However, other proteins bearing this modification in vivo are still largely unknown. Here, we describe a highly reliable method combining glycosidase treatment with LC-MS analyses to identify mammalian O-mannosylated proteins from tissue sources. Our workflow identified T-cadherin (H-cadherin, CDH13) as a novel O-mannosylated protein. In contrast to known O-mannosylated proteins, single mannose residues (Man-α-Ser/Thr) are attached to this cell adhesion molecule. Conserved O-glycosylation sites in T-, E- and N-cadherins from different species, point to a general role of O-mannosyl glycans for cadherin function.